Producing music - Hepworth-Sawyer, Russ; Hodgson, Jay; Marrington, Mark (Perspectives on music production series, 2019)
During the last two decades, the field of music production has attracted considerable interest from the academic community, more recently becoming established as an important and flourishing research discipline in its own right.